Collagen loaded nano-sized surfactant based dispersion for topical application: formulation development, characterization and safety study. (1st June 2014) - Ahmad, Iqbal; Akhter, Sohail; Ahmad, Mohammad Zaki; Shamim, Mohd; Rizvi, Mushahid Alam; Khar, Roop K.; Ahmad, Farhan J.
Abstract: Collagen, a high molecular weight, hydrophilic and highly abundant protein is known to have anti-ageing, anti-wrinkle, anti-acne, anti-scar and wound healing properties. High molecular weight and hydrophilic nature hinder its effective topical delivery. So, the objective of present study was to develop effective topical nano-surfactant dispersion (NSD) for collagen delivery. NSD was prepared from sorbitan monostearate (Span60) and cholesterol using ethanol injection method followed by probe sonication. NSD was characterized for entrapment efficiency (%EE), size and size distribution (Z-avg and polydispersity index (PDI)), shape, zeta-potential (ζ), in vitro drug release, skin hydration and skin irritation test and histopathological examination. Optimized NSD (NSD3) had %EE, z-avg, PDI and ζ-potential of 77.56% ± 1.09%, 158.1 ± 2.31 nm, 0.211 and −17.2 ± 0.64 mV, respectively. In in vivo skin hydration test, NSD treatment showed nearly 2.5-fold and 3-fold increase in the thickness of stratum corneum (SC) as compared to the collagen gel treated and untreated skin, respectively. The mean scores of skin irritation test in two animal species, rats and rabbits, were found to be 1.42 ± 1.01 and 1.71 ± 0.29, respectively, indicating the non-irritant nature of collagen loaded NSD. Histopathology of the skin after application of developed NSD showed non-significant changes in skin anatomy indicating its safe nature.